2021
DOI: 10.2147/copd.s289099
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Pressure Domiciliary Non-Invasive Ventilation on Clinical Outcomes in Patients with Severe COPD Regardless Having Hypercapnia

Abstract: Background The effectiveness of non-invasive home ventilation in patients with severe chronic obstructive pulmonary disease (COPD) is lacking. Non-invasive home ventilation might be more effective when high ventilator settings are used. However, high ventilator settings might reduce patient adherence. We have developed a multidisciplinary approach (ventilation practitioners, 24 hours support of respiratory nurses, physicians) to non-invasive ventilation aimed at optimizing patient adherence using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…On the other hand, one previous study showed a survival benefit without a change in hypercapnia [17]. Moreover, more recently, Theunisse and co-workers showed that low pressure HNIV aimed to optimize acceptance and adherence may significantly reduce admission rate, duration of hospitalization, symptoms and quality of life at 1 year in severe COPD patients irrespective of the presence of hypercapnia [21]. Therefore, further investigations are needed to show if chronic hypercapnia and the reduction or normalization of PaCO 2 should be considered, respectively, the only enrollment criteria and target of successful HNIV.…”
Section: How To Ventilate: Choosing a Ventilator And Setting For Succ...mentioning
confidence: 99%
“…On the other hand, one previous study showed a survival benefit without a change in hypercapnia [17]. Moreover, more recently, Theunisse and co-workers showed that low pressure HNIV aimed to optimize acceptance and adherence may significantly reduce admission rate, duration of hospitalization, symptoms and quality of life at 1 year in severe COPD patients irrespective of the presence of hypercapnia [21]. Therefore, further investigations are needed to show if chronic hypercapnia and the reduction or normalization of PaCO 2 should be considered, respectively, the only enrollment criteria and target of successful HNIV.…”
Section: How To Ventilate: Choosing a Ventilator And Setting For Succ...mentioning
confidence: 99%